History in the Hands of Students: Crafting Role-Playing Games as an Innovative Didactic Tool - Witek-Dryjańska, Katarzyna (Sensus Historiae, 2025)
All participants in the roundtable discussion on the topic: Students as Authors of Their Own Historical Knowledge in History Lessons, agreed that students should create their own historical knowledge, putting forward numerous proposals for change in the education system. This discussion took place during the 1st Student and Doctoral Congress of History Didactics held on 9-10 May 2024 at the Faculty of History of Adam Mickiewicz University. It was one of the four discussions held as part of the World Café meeting (a collaborative dialogue process). The aim of this article is to present the recommendations for change relating to historical education in schools, developed during the roundtable discussion, and an attempt to facilitate their implementation in contemporary education using a didactic tool that can be a historical role-playing game.